2012
DOI: 10.1002/adfm.201201413
|View full text |Cite
|
Sign up to set email alerts
|

Compact Saloplastic Poly(Acrylic Acid)/Poly(Allylamine) Complexes: Kinetic Control Over Composition, Microstructure, and Mechanical Properties

Abstract: Durable compact polyelectrolyte complexes (CoPECs) with controlled porosity and mechanical properties are prepared by ultracentrifugation. Because the starting materials, poly(allylamine hydrochloride) (PAH) and poly(acrylic acid sodium salt) (PAA), are weak acids/bases, both composition and morphology are controlled by solution pH. In addition, the nonequilibrium nature of polyelectrolyte complexation can be exploited to provide a range of compositions and porosities under the influence of polyelectrolyte add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 46 publications
4
89
1
Order By: Relevance
“…The extent of porosity depends on how the CoPECs are prepared. It was found that equimolar polyallylamine(PAH)/polyacrylate (PAA) CoPECs, formed and stored in 2.5 M NaCl, show pores with a typical diameter on the order of 20–40 μm . These are roughly the same size as PEMU microcapsules, which exhibit excess osmotic pressure inside the capsule due to excess polyelectrolyte as is also thought to be the case with strongly swollen, hydrated polylysine/hyaluronic acid multilayers .…”
Section: Compaction By Ultracentrifugationmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of porosity depends on how the CoPECs are prepared. It was found that equimolar polyallylamine(PAH)/polyacrylate (PAA) CoPECs, formed and stored in 2.5 M NaCl, show pores with a typical diameter on the order of 20–40 μm . These are roughly the same size as PEMU microcapsules, which exhibit excess osmotic pressure inside the capsule due to excess polyelectrolyte as is also thought to be the case with strongly swollen, hydrated polylysine/hyaluronic acid multilayers .…”
Section: Compaction By Ultracentrifugationmentioning
confidence: 99%
“…When the centrifugation speed was reduced during CoPEC formation, the size of the large pores increased . Before centrifugation, the solution of polyelectrolyte complexes not only contained large blobs of complexes but also very large voids with typical sizes up to 200 μm.…”
Section: Compaction By Ultracentrifugationmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric complexes can be produced by mixing polymers with complementary noncovalent interactions in bulk solution or sequentially at interface of solid substrates and polymer solutions . Given that various polymers bearing complementary interactions can be employed to prepare polymeric complexes, polymeric composite materials based on polymeric complexes can possess various compositions, controllable cross‐linking density, and well‐tailored mechanical properties . During the formation of polymeric complexes, polymers with self‐assembly ability can generate well‐designed micro‐/nanosized structures, which provide a facile way to further tailor the mechanical properties of the resultant materials .…”
Section: Summary Of Mechanical Properties Of the Paa–pvpon Compositesmentioning
confidence: 99%
“…To stabilize fibrous hydrogels in aqueous media, thermal or vapor‐phase crosslinking is required which impedes their applications. Polyelectrolyte complexes have been used to improve the stability of fibrous hydrogels in aqueous solutions . A polyelectrolyte complex is formed by mixing oppositely charged polyelectrolytes such as poly(acrylic acid) (PAA) and poly(allyl amine hydrochloric acid) or PAA and chitosan (CS) in solutions with controlled polymer ratio and pH.…”
Section: Introductionmentioning
confidence: 99%